ANALYZING REGIONAL LEADING ECONOMIC SECTORS FOR GRDP AND INVESTMENT PROJECTIONS : EVIDENCE FROM INDONESIA - Sutanti Sutanti; Azizatul Munawaroh; Atika Rahmi; Zaidah Rizkiyah (Multidisciplinary Research Studies in Social Sciences, 2025)
Sustainable economic growth can be maintained in part through integrated economic development planning to foster leading sectors. This is also necessary for Banten Province, which experienced a contraction in economic growth during the Covid-19 pandemic. Although Banten’s economic growth rate has increased year by year—except in 2020—this does not diminish the potential of its leading sectors. This study aims to :1).Identify the leading economic sectors in Banten Province that meet the criteria of having competitive, comparative, and prospective advantages. 2).Project the Gross Regional Domestic Product (GRDP) of Banten Province for the years 2024 to 2026. 3).Calculate the amount of investment required by Banten Province to achieve the targeted/projected economic growth during the 2024–2026 period. The data used in this study are secondary time series data spanning ten years from 2014 to 2023, consisting of GRDP data for Banten Province, Indonesia’s GDP, Banten Province’s Regional Budget (APBD), and Gross Fixed Capital Formation (GFCF) data. These were obtained from the Central Bureau of Statistics (BPS) and BPS of Banten Province. Based on the calculations of Location Quotient (LQ), Dynamic Location Quotient (DLQ), and Shift-Share Analysis using 2014–2023 base data, the leading sector in Banten Province is the Water Supply, Waste Management, Waste and Recycling sector. This sector qualifies as a base sector according to the LQ, shows rapid growth as per DLQ, and is identified as a fast-growing, geographically advantageous sector with a positive National Share value.The most suitable trend model for projecting the GRDP at constant prices for Banten Province is the quadratic/parabolic trend model, as it has the lowest mean absolute error. The GRDP projections at constant prices are as follows : 2024: IDR 510,576.42 billion; 2025: IDR 521,638.02 billion; 2026: IDR 531,801.37 billion. Based on ICOR calculations and GRDP projections, the required investment for Banten Province is: 2024: IDR 14,770.21 billion; 2025: IDR 51,880.84 billion; 2026: IDR 47,667.93 billion.Keywords : : Leading Sector, Location Quotient (LQ), Dynamic Location Quotient (DLQ), Shift-Share Analysis, Incremental Capital Output Ratio (ICOR).